Nursing care and ethical issues surgen from the technological health advance - Escobar-Castellanos, Blanca; Cid-Henríquez, Patricia (Acta Bioethica, 2018)
Background: Nurses are exposed to face ethical conflicts because the responsibilities associated with caring for people and the fact of working in a health field ever more tech and complex. Objective: Analyze the ethical issues that affect nursing care, caused by the advance of technology in health services. Development: Nurses are responsible for the use of technology, so it requires professional training in the use and application of therapeutic or diagnostic techniques, should be used ethical criteria and values of discipline with a view holistic and humanistic care of people. An approach healthcare based on ethics implies that the nurse considers the human being with absolute respect and dignity. Conclusions: Nursing must demonstrate humanized care in all actions executed by applying the ethical knowledge, attitudes and values towards caring person.